Suckling behaviour in the pipistrelle bat ( Pipistrellus pipistrellus ) ... - Hughes, P. M.; Speakman, J. R.; Jones, G.; Racey, P. A. (Zenodo, 1989)
(Uploaded by Plazi for the Bat Literature Project) A sub‐colony of 20 pipistrelle bats was studied during late pregnancy and lactation. Seventeen females gave birth to single young, with 16 young surviving to weaning. Free association and flight were permitted, and mother‐infant pairs were identified and marked on the day of birth (day 0). Suckling associations were identified daily (n = 195) and females were never found suckling young other than their own. A series of choice experiments using young aged 0–10 days and 15–25 days indicated that females would permit only their own offspring to suckle during both early and late lactation. During early lactation, mothers actively selected their young and encouraged suckling but did not do so during late lactation. Mothers were most often indifferent to approaches by alien young but occasionally aggressively rejected them. Mothers never aggressively rejected their own young but frequently were indifferent to them. Young attempted to suckle from any mother without ...